INNOVATIVE DEVELOPMENT OF ENGINEERING – THE BASIS OF MODERNIZATION OF THE RUSSIAN PROCESSING INDUSTRY - V. N. Borisov; E. A. Balagurova (Модернизация, инновация, развитие, 2016)
Given the present state of Russian machine building industry, noticeable innovative development of domestic machine building industry may hardly be expected within the frames of the announced Russian economy modernization program. In order to update Russian machine-building industry, utmost foreign investment should be attracted.